Pengaruh Perilaku Doom Spending dan Kecerdasan Emosional terhadap Kemampuan Berinvestasi dengan Kecerdasan Intelektual sebagai Variabel Moderating di Kalangan Mahasiswa Generasi Z di Jawa Timur - Kusuma, Nyo Tersa Dofora; Wany, Eva; Prayitno, Budi Prayitno (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2025)
Doom spending behavior, which refers to the tendency to consume triggered by anxiety about the future, and emotional intelligence, which is related to the ability to manage emotions, are believed to influence investment decisions among Gen Z in East Java. Meanwhile, intellectual intelligence, as a measure of cognitive ability, is hypothesized to moderate the relationship between the two variables and investment ability. Therefore, this study aims to determine the extent to which doom spending behavior and emotional intelligence influence investment ability moderated by intellectual intelligence. The research method used is quantitative with data collection techniques through questionnaires distributed to Generation Z students at several universities in East Java. The results of the study are expected to provide insight into the psychological factors that influence investment behavior among students and the importance of intellectual intelligence in directing better investment decisions. This study is also expected to be a consideration for the development of financial education programs for Generation Z.